Assessing the Transitional Impact and Mental Health Consequences of the COVID-19 Pandemic Onset - Heanoy, Eamin Z.; Shi, Liangzi; Brown, Norman R. (Frontiers in Psychology, 2021)
In this article, we report the results of a survey of North American adults (n = 1,215) conducted between March 24, 2020, and March 30, 2020, at the onset of the COVID-19 Pandemic. Respondents completed the COVID-TIS (Transitional Impact Scale-Pandemic version) and the 21-item DASS (Depression, Anxiety, and Stress Scale), indicated their level of COVID-infection concern for themselves and close others, and provided demographic information. The results indicated: (a) during its early stage, the Pandemic produced only moderately levels of material and psychological change; (b) the Pandemic produce mild to moderate levels of psychological distress; (c) respondents who lost their jobs as a result of the Pandemic experienced more change and more psychological distress than those who did not, and (d) younger respondents and less-well educated ones experienced more psychological distress than older respondents. Unexpectedly, (e) respondents indicated that they were more concerned that friends and family members would become infected with COVID-19 than that they would be. We conclude by speculating that these results are driven less by the immediate changes brought about by the Pandemic and more by uncertainty concerning its long term economic and social impact.